Anthropometric and Body Composition Characteristics of Soccer Athletes in Yogyakarta - Neni Trilusiana Rahmawati Neni Trilusiana Rahmawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: There is considerable evidence indicating that champions of various sports events differ significantly in their physical and physiological characteristics. It is not only the intersport differences, but also in the same sport, depending upon playing position.Objective: To study anthropometric characteristics and body composition of forwards, half-liners, backs and goalkeepers of soccer athletes in Yogyakarta.Methods: 60 soccer athletes in Yogyakarta, aged 17 to 32 year were recruited in the study. Body height and weight, shoulder and pelvic breadth, trunk length, and body fat were measured and compared among subjects of different playing positions. Analysis of variance was used as statistical tests to express the difference between anthropometric characteristics and body composition among forwards, half-liners, backs and goalkeepers.Results: The result showed that the goalkeepers had the highest score of average height, weight, shoulder and pelvic breadth, trunk length and body fat. There were significant differences of height, weight and body fat among the four subgroups of soccer athletes.Conclusion: There were similarities of somatotype distributions between Yogyakarta soccer athletes and world soccer athletes.Key words: sport anthropology - soccer athletes - anthropometry - body composition